2022
DOI: 10.3390/ijms23105460
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis on MS-Based Proteomics Applied to Human Peripheral Fluids to Assess Potential Biomarkers of Bipolar Disorder

Abstract: Bipolar disorder (BD) is a clinically heterogeneous condition, presenting a complex underlying etiopathogenesis that is not sufficiently characterized. Without molecular biomarkers being used in the clinical environment, several large screen proteomics studies have been conducted to provide valuable molecular information. Mass spectrometry (MS)-based techniques can be a powerful tool for the identification of disease biomarkers, improving prediction and diagnosis ability. Here, we evaluate the efficacy of MS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 97 publications
1
4
1
Order By: Relevance
“…Regarding biological processes and pathways, our findings support previous studies [16]–[19], indicating that the interplay between the complement system and coagulation cascade is involved in the etiology and progression of BD. The complement system originates from the serine protease reaction cascade, sharing a common ancestry with the coagulation factors encoded by the same ancestor genes [20], [21].…”
Section: Discussionsupporting
confidence: 90%
“…Regarding biological processes and pathways, our findings support previous studies [16]–[19], indicating that the interplay between the complement system and coagulation cascade is involved in the etiology and progression of BD. The complement system originates from the serine protease reaction cascade, sharing a common ancestry with the coagulation factors encoded by the same ancestor genes [20], [21].…”
Section: Discussionsupporting
confidence: 90%
“…In fact, of the six studies reporting the illness duration, four of them are studies that also compared SCZ and BD groups. The lack of interest in the illness duration is very different from what is observed in BD studies [110], where this parameter is reported in the majority of the studies.…”
Section: Strengths and Limitationscontrasting
confidence: 71%
“…Significant differences related to diagnostic criteria used, medical and psychiatric comorbidities reported, psychopharmacological treatment and its duration, as well as the sociodemographic variables such as age, illness duration, gender balance, diet, and use of tobacco, alcohol, or other psychoactive substances, among others, were observed in the selected studies. These limitations were also observed in a BD systematic review [110], suggesting common limiting factors across the psychiatric disorders studies using MS proteomics approaches, thus highlighting the need for more standardized, or at least more controlled, cohort characteristics.…”
Section: Strengths and Limitationsmentioning
confidence: 93%
“…In addition to the in ammatory response involving cytokines, another critical and essential mechanism in in ammation is the coagulation cascade activation since thrombin -the enzyme that catalyzes the conversion of brinogen to brin -has pro-in ammatory functions [71], [72]. Data from patients' blood analyzed by mass spectrometry and gene ontology showed the involvement of complement and coagulation cascade in BD physiopathology by identifying speci c proteins such as the third component of complement and apolipoprotein A involved in these processes [73], [74]. A pilot study also indicated the dysregulation of the coagulation cascade in treated schizophrenia and BD patients through proteome analysis, reinforcing the importance of these biological processes in psychiatric disorders [75].…”
Section: Biological Processes Related To Bd Statesmentioning
confidence: 99%